How does podocyte damage result in tubular damage? - Kriz, Wilhelm; Elger, Marlies; Hosser, Hiltraud; Hähnel, Brunhilde; Kränzlin, Bettina; Gretz, Norbert (Kidney & blood pressure research, 1999)
Severe podocyte damage including detachment from the GBM leads to adhesion of the glomerular tuft to Bowman’s capsule, thus to a local loss of the separation of the tuft from the interstitium. Perfuse